Hypertrophy nutrition: Stimulating an anabolic response with para-workout nutrition - McKillop, D. (Journal of Australian Strength and Conditioning, 2012)
Countless studies in the past have continued to assess the nutritional needs of an athlete seeking increased muscular hypertrophy, however few are yet to review nutritional principles as a single protocol. Instead, an emergence of studies focusing on pre-training, intra-training and post-training strategies as a solitary source to improve muscular hypertrophy continue to grow. While these papers are informative, they lack real world application. In this paper, a review of the literature was used to provide an up to date, scientific approach to para-workout nutrition. In doing so, para-workout nutrition can be describe as any nutrition used around the workout and in essence will utilise all three phases of pre, intra and post-workout nutrition to provide an evidence based practical implementation of which nutrients are most important in each phase, why they are important and what dosage is necessary to elicit the most efficient results. Studies have consistently shown individuals implementing para workout supplementation protocols utilising nutrients such as proteins, carbohydrates and creatines increase protein synthesis, improve performance and result in greater muscular hypertrophy. Individuals looking to enhance their anabolic response to training should look to ingest a formula consisting of10-20g of Whey Protein, 0.1g/kg of body weight of Amino Acids, 0.2-1.0g/kg of body weight of carbohydrates (intensity relevant) and 0.1g/kg of body weight of Creatine monohydrate